2007
DOI: 10.1186/1471-2407-7-180
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for Luminal epithelial like ER positive subtype of human breast cancer

Abstract: Background: Generation of novel spontaneous ER positive mammary tumor animal model from heterozygous NIH nude mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Abundant research has revealed that hormone receptor (i.e., ER) status is one of the most important features of BRCA [36,37]. Epidemiological research has shown that about 70% of BRCA patients are [38]. Nevertheless, ER-positive BRCA still constitutes a more heterogeneous group for diagnosis and treatment [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Abundant research has revealed that hormone receptor (i.e., ER) status is one of the most important features of BRCA [36,37]. Epidemiological research has shown that about 70% of BRCA patients are [38]. Nevertheless, ER-positive BRCA still constitutes a more heterogeneous group for diagnosis and treatment [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…About one million women worldwide are diagnosed with BC every year (1,2). So it is very important to prevent tumorigenesis and treat cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although not deliberately genetically engineered, brother-sister matings of heterozygous NIH nude mice resulted in development of a line of mice with high serum estrogen levels in which 62% of females develop ERα positive metastatic mammary cancers by a mean age of seven months (Kumar, et al 2007) (Table 1E). Mammary adenocarcinomas appear only in breeding females.…”
Section: Spontaneous Er+ Mammary Cancer Nude Mouse Modelmentioning
confidence: 99%
“…There is a strong need for ER+ models that reliably develop metastatic disease. Further characterization of the model developed in nude mice (Kumar et al 2007) is required before it can be effectively used for experiments that might address the pathophysiology of ER+ metastatic disease. Another approach to developing more sophisticated models reflective of individual ER+ breast cancer sub-types will be to combine transgenic Esr1 expression with other genetic manipulations as was accomplished for both TAg expression and loss of Brca1/p53 .…”
Section: Future Directionsmentioning
confidence: 99%